An Integrative Model of Patient-Centeredness – A Systematic Review and Concept Analysis - Scholl, Isabelle; Zill, Jördis M.; Härter, Martin; Dirmaier, Jörg (PloS one, 2014)
Existing models of patient-centeredness reveal a lack of conceptual clarity. This results in a heterogeneous use of the term, unclear measurement dimensions, inconsistent results regarding the effectiveness of patient-centered interventions, and finally in difficulties in implementing patient-centered care. The aim of this systematic review was to identify the different dimensions of patient-centeredness described in the literature and to propose an integrative model of patient-centeredness based on these results. Protocol driven search in five databases, combined with a comprehensive secondary search strategy. All articles that include a definition of patient-centeredness were eligible for inclusion in the review and subject to subsequent content analysis. Two researchers independently first screened titles and abstracts, then assessed full texts for eligibility. In each article the given definition of patient-centeredness was coded independently by two researchers. We discussed codes within the research team and condensed them into an integrative model of patient-centeredness. 4707 records were identified through primary and secondary search, of which 706 were retained after screening of titles and abstracts. 417 articles (59%) contained a definition of patient-centeredness and were coded. 15 dimensions of patient-centeredness were identified: essential characteristics of clinician, clinician-patient relationship, clinician-patient communication, patient as unique person, biopsychosocial perspective, patient information, patient involvement in care, involvement of family and friends, patient empowerment, physical support, emotional support, integration of medical and non-medical care, teamwork and teambuilding, access to care, coordination and continuity of care. In the resulting integrative model the dimensions were mapped onto different levels of care. The proposed integrative model of patient-centeredness allows different stakeholders to speak the same language. It provides a foundation for creating better measures and interventions. It can also be used to inform the development of clinical guidance documents and health policy directives, and through this support the shift towards patient-centered health care.